1979
DOI: 10.1111/j.1440-1827.1979.tb00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Histochemistry of Non‐hodgkin's Lymphomas

Abstract: Fifty-two cases of non-Hodgkin's lymphomas were studied with enzyme histochemical methods. Forty-four cases of these were also investigated for surface markers with immunological techniques, and results of histochemical, routine histological and immunological observations were correlated. Twenty-one of 27 B-cell lymphomas showed prominent ATPase activity, while all 13 T-cell lymphomas, except one case, did not show such activity. Nodular lymphomas, though of B-cell nature, were often negative for ATPase and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There are several reports on the distribution of ALP-positive lymphocytes in normal lymphoid tissue (1,2,3,4,12,13). Nanba et a1 (2), Pinkus & Said (3) and Poppema et a1 (4) reported that ALP-positive lymphocytes were found mostly in primary follicles and MZs of secondary follicles but were hardly seen in GCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports on the distribution of ALP-positive lymphocytes in normal lymphoid tissue (1,2,3,4,12,13). Nanba et a1 (2), Pinkus & Said (3) and Poppema et a1 (4) reported that ALP-positive lymphocytes were found mostly in primary follicles and MZs of secondary follicles but were hardly seen in GCs.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of alkaline phosphatase (ALP) in non-Hodgkin's lymphomas has already been reported (1,2,3,4,5). The ALP activity has been most consistently observed in cases of B-cell lymphomas, especially ML, diffuse, small cleaved cell and intermediate lymphocytic lymphomas.…”
mentioning
confidence: 96%
“…Thus, we consider that Alk-P is not useful for differentiating between the types of low grade B cell lymphomas. Similarly, Nanba et al [31] and Mikata et al [32] also reported that neoplastic lympho cytes showed Alk-P positivity in some cases with various types of B cell lymphomas, regardless of the grade of ma lignancy. Further investigations arc necessary to elucidate the implication of the expression on Alk-P in the neoplas tic B cells.…”
mentioning
confidence: 99%